PELAKSANAAN FUNGSI ADMINISTRATOR KEPALA SEKOLAH MENENGAH ATAS NEGERI 10 KOTA PADANG - Yulianto Santoso (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2016)
This research based on the lack of effectiveness of the administrator function of the Principal Sekolah Menengah Atas Negeri (SMAN) 10 Padang. This research is designed to reveal teachers perception on the implementation administrator function of principal, which will be seen from: 1) teachers perception about implementation administrator function of principal of SMAN 10 Padang related to curriculum administration, 2) teachers perception about implementation administrator functionof principal of SMAN 10 Padang related to personnel administration, 3) teacher perception about implementation administrator function of principal of SMAN 10 Padang related to school facilities and infrastructure administration, and 4) teacher perception about implementation of administrator function of the principal of SMAN 10 Padang related to financial administration. This descriptive research with the population of all teachers who have the Civil Servants status at SMAN 10 Padang with the number to 61 people. Sample of this research amounted to 36 people, taken using the formula Cohran. Sampling technique is based on stratified proportional random sampling. The tool used for data collection is a questionnaire that has been tested for its validity and reliability. Data were analyzed using percentage and average formulas. The results of this research indicated that the general perception of teachers on the implementation of administrator function of the principal is in category good with an average score of 3.87. Furthermore, teachers perceptions regarding to the implementation of curriculum administration, personnel administration, facilities and infrastructure administration and financial administration are (4.19, 3.63, 3.86 and 3.81), respectively, where the whole is in good category